1996
DOI: 10.1111/j.1467-8624.1996.tb01892.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning in Young Children: Fantasy and Information Retrieval

Abstract: The present article examines 2 predictions concerning conditional reasoning in children derived from Markovits's model of conditional reasoning. The first claims that children under 12 years of age should be able to respond correctly to uncertain logical forms if the premises and context enable them to access pertinent counterexamples from memory. The second concerns the effect of reasoning in a fantasy context. Previous studies have established that young children can correctly respond to certain reasoning pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 23 publications
2
33
0
4
Order By: Relevance
“…Previous research has yielded similar results for each logical form (e.g. Ishida, 1980;Markovits, 1995;Markovits, Fleury, Quinn, & Venet, 1998;Markovits, Venet, Janveau-Brennan, Malfait, Pion, & Vadeboncoeur, 1996). The present study validates the findings of previous studies by directly comparing the inference performance of different age groups in a single study, using the same tasks.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous research has yielded similar results for each logical form (e.g. Ishida, 1980;Markovits, 1995;Markovits, Fleury, Quinn, & Venet, 1998;Markovits, Venet, Janveau-Brennan, Malfait, Pion, & Vadeboncoeur, 1996). The present study validates the findings of previous studies by directly comparing the inference performance of different age groups in a single study, using the same tasks.…”
Section: Discussionsupporting
confidence: 80%
“…Byrnes & Overton, 1986;Ishida, 1980) or by using conditional propositions that readily produce other possibilities (e.g. Markovits et al, 1998;Markovits et al, 1996). These results suggested that even preschoolers and elementary students had the ability to infer conclusions from the invalid forms.…”
Section: Discussionmentioning
confidence: 65%
“…Finally here, Crone et al concluded that the evidence that activation in RLPFC associated with relational integration increases as a function of age suggests that development of the RLPFC integration mechanism occurs over the age range (8-12 years). This is the same age range as identified as critical to the initial emergence of transitivity as a deductive competence and also many other domains of deductive reasoning (Bouwmeester & Sijtsma, 2007;Chapell & Overton, 2002;De Neys & Vanderputte, 2011;Markovits et al, 1996;Markovits & Thompson, 2008;Morsanyi & Handley, 2008;Verweij et al, 1996;Wright, 1998a, b).…”
Section: Dual Transitive 46mentioning
confidence: 99%
“…For example, Markovits et al (1996) investigated conditional reasoning in 7 to 12 year-olds. The tasks were framed using pretend contexts, such as the likes and dislikes of people on a pretend planet.…”
Section: Dual Transitive 38mentioning
confidence: 99%
“…This is not because children do not reason according to the dictates of Mental Models. Children as young as those in the present study show a pattern of logical inference similar to adults (Markovits, Venet, Janveau-Brennan, Malfait, Pion, & Vadeboncoeur, 1996): they are accurate on Modus Ponens arguments and make errors on Modus Tollens arguments. If their performance in the present study were the result of such logical operations, they would not show the same pattern of reasoning (e.g., a logic/structure effect) as do the adults in the study.…”
Section: Mental Modelsmentioning
confidence: 63%